1983
DOI: 10.1128/jcm.17.5.781-786.1983
|View full text |Cite
|
Sign up to set email alerts
|

Heptakis(2,6-O-dimethyl)beta-cyclodextrin: a novel growth stimulant for Bordetella pertussis phase I

Abstract: The effect of cyclodextrins on the growth of Bordetella pertussis Tohama phase I in synthetic medium was evaluated. The addition of cyclodextrins, especially heptakis(2,6-0-dimethyl)p-cyclodextrin (MePCD), to a complete synthetic medium such as Stainer-Scholte medium gave the same number of individual colonies and growth rates as those on Bordet-Gengou medium. Furthermore, with the addition of MePCD, growth inhibition by fatty acids such as oleic or palmitic acid was overcome and normal cell growth was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…Futhermore, bearing in mind that Me/3CD also enhances the release of the major component of outer membrane, namely the lipopolysaccharide (LPS), it is possible that cyclodextrin increases the level of extracellular antigens by stimulating their release, destabilising the outer membrane [12,24]. This hypothesis is in accordance with the observation that cyclodextrin forms inclusion complexes with hydrophobic compounds, such as fatty acids [8,9]. Since the lipopolysaccharide contains several fatty acids [25], Me/3CD may interact with this component of outer membrane.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Futhermore, bearing in mind that Me/3CD also enhances the release of the major component of outer membrane, namely the lipopolysaccharide (LPS), it is possible that cyclodextrin increases the level of extracellular antigens by stimulating their release, destabilising the outer membrane [12,24]. This hypothesis is in accordance with the observation that cyclodextrin forms inclusion complexes with hydrophobic compounds, such as fatty acids [8,9]. Since the lipopolysaccharide contains several fatty acids [25], Me/3CD may interact with this component of outer membrane.…”
Section: Resultssupporting
confidence: 56%
“…The discovery that addition of 2,6-O-dimethyl-/3-cyclodextrin (Me/~CD) to the Stainer-Scholte (SS) [6] medium led to an enhanced level of AC, proved to be helpful [7]. Other authors have reported that cyclodextrin also increased the level of the other important soluble immunogens of B. pertussis such as pertussis toxin (PT) and filamentous hemagglutinin (FHA) [8][9][10][11]. However, the way which this compound enhances the yield of extracellular antigens, and in particular that of AC, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid culture of B. pertussis used modified Stainer-Scholte (SS) medium (Stainer & Scholte, 1970;Schneider & Parker, 1982) supplemented with 0.5% casamino acids at 35°C with shaking at 300 r.p.m. SS cultures for b-galactosidase measurements also contained 500 lg mL À1 of heptakis (2,6-di-O-methyl)-b-cyclodextrin (Imaizumi et al, 1983). Escherichia coli strains were cultured on Luria Bertani agar or broth.…”
Section: Bacterial Strains and Cultivationmentioning
confidence: 99%
“…They were plated on Bordet Gengou (BG) agar (Bordet and Gengou, 1906) and incubated for 2 days at 37°C. Bacteria were used to inoculate small volumes of modified Stainer and Scholte (SS) medium (Imaizumi et al, 1983), and the cultures were grown overnight under orbital shaking at 37°C. These small cultures were used to inoculate larger volumes of modified SS medium, and the cultures were grown for 24 h under agitation at 37°C until late exponential phase.…”
Section: Secretion Signal In Tps Pathway 377mentioning
confidence: 99%